2010
DOI: 10.1074/jbc.m110.124891
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of Mouse Monocyte Chemoattractant Protein 1 (MCP1) Mediates MCP1 Dimerization while Blocking Its Chemotactic Potency

Abstract: The extracellular protease plasmin cleaves mouse MCP1 (monocyte chemoattractant protein 1) at lysine 104, releasing a 50-amino acid C-terminal domain. The cleavage event increases the chemotactic activity of MCP1 and, by doing so, promotes the progression of excitotoxic injury in the central nervous system in pathological settings. The mechanism through which the cleavage event enhances MCP1-mediated chemoattraction is unknown; to investigate it, we use wild-type and mutant forms of recombinant MCP1. Full-leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 62 publications
(61 reference statements)
12
66
0
Order By: Relevance
“…However, the effect was more potent in MCP1 -/-mice than in wild-type mice. It has been shown that MCP1 binds to and reduces membrane 1491 Truncated MCP1 disrupts the blood-brain barrier CCR2 levels (probably through endocytosis) (Jung et al, 2009;Yao and Tsirka, 2010). The dramatic change observed in MCP1 -/-mice could be due to higher membrane CCR2 density, as in the absence of MCP1 there would be no recycling of CCR2 off the plasma membrane.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the effect was more potent in MCP1 -/-mice than in wild-type mice. It has been shown that MCP1 binds to and reduces membrane 1491 Truncated MCP1 disrupts the blood-brain barrier CCR2 levels (probably through endocytosis) (Jung et al, 2009;Yao and Tsirka, 2010). The dramatic change observed in MCP1 -/-mice could be due to higher membrane CCR2 density, as in the absence of MCP1 there would be no recycling of CCR2 off the plasma membrane.…”
Section: Discussionmentioning
confidence: 96%
“…These data suggest that upon MCP-1 binding to endothelial CCR2, a property that all MCP-1 mutants that retain the N-terminal portion of the protein exhibit, an increase in cortical actin is observed. However, the next step of the process, the internalization of CCR2 and re-arrangements of actin cytoskeleton to allow the cells to retract/reorganize the TJPs, is taking place only when the active FL-and K104Stop-MCP-1 proteins are present (Yao and Tsirka, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations